Ceramic coating for refractories protection against carbon oxidation, Part 1: Protection mechanisms - Garcia Dos Santos, I.; Cruz, F.; Paskocimas, C. A.; Nascimento Silva, S.; Marques, O. R.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (My University, 1999)
For retarding carbon oxidation in refractories during the preheating of metallurgical furnaces, a ceramic coating, made mainly of sodium phosphosilicate and clay was developed. The coating presents high adherence to the substrate with no swelling. The coating was characterized by thermal analysis, X-ray diffraction at room temperature (XRD) and at high temperature (HTXRD), X-ray fluorescence and scanning electronic microscopy (SEM). The glass transition temperature is reached at 800 °C and only glassy phase is observed above this temperature. Thus the mechanism of protection seems to be the formation of a glassy phase on the surface of the refractory, and the coating tends to be more efficient at temperatures higher than 800 °C.
Keywords: Clay; Fluorescence; Glass transition; Oxidation; Protective coatings; Refractory materials; Scanning electron microscopy; Substrates; Thermal effects; Thermoanalysis; X ray diffraction; Carbon oxidation; X ray fluorescence; Ceramic coatings